The puppet masters : how the corrupt use legal structures to hide stolen assets and what to do about it - Does de Willebois, Emile van der; Sharman, J. C.; Harrison, Robert (World Bank e-Library., 2011)
Billions in corrupt assets, complex money trails, strings of shell companies and other spurious legal structures. These form the complex web of subterfuge in corruption cases, behind which hides the beneficial owner- the Puppet Master and beneficiary of it all. Linking the beneficial owner to the proceeds of corruption is notoriously hard. With sizable wealth and resources on their side, they exploit transnational constructions that are hard to penetrate and stay aggressively ahead of the game. Nearly all cases of grand corruption have one thing in common. They rely on corporate vehicles- lega.